On the application of signal compression using Golay's codes sequences in ultrasound diagnostic - Nowicki, A.; Secomski, W.; Litniewski, J.; Trots, I.; Lewin, P. A. (Archives of Acoustics, 2003)
The issue of maximizing penetration depth with concurrent retaining or enhancement of image resolution constitutes one of the time invariant challenges in ultrasound imaging. Concerns about potential and undesirable side effects set limits on the possibility of overcoming the frequency dependent attenuation effects by increasing peak acoustic amplitudes of the waves probing the tissue. To overcome this limitation a pulse compression technique employing 8 bits Complementary Golay Code (CGS) was implemented at 4 MHz. In comparison with other, earlier proposed, coded excitation schemes, such as chirp, pseudo-random chirp and Barker codes, the CGS allowed virtually side lobe free operation. Computer simulation results for CGS pulse compression are presented. Next, the images of RMI tissue phantom generated by those two excitations schemes are presented. Identical peak power conditions in the experimental setup were implemented with the earlier mentioned 8 bits CGC and 2 periods tone burst. Experimental data indicate that the quality of CGS images is comparable to that acquired using conventional pulse imaging. CGS exhibited signal-to-noise ratio (SNR) gain of 9.6 dB with the axial resolution being virtually the same for both transmitting schemes.